Identification and characterization of a male-specific region in largemouth bass (Micropterus Salmoides) by whole-genome sequencing, resequencing and genomics comparison - Zhang, Xinhui; Dong, Junjian; Ruan, Zhiqiang; Gao, Fengying; Zhou, Wenchuan; You, Xinxin; Chen, Jieming; Shi, Qiong; Ye, Xing; Sun, Chengfei (Frontiers in Marine Science, 2025)
IntroductionCompared to mammals and birds, sex-determining genes differ in most fish species. Largemouth bass (Micropterus Salmoides) is one of the most important cultured fish species in China, and there are growth differences between males and females. However, its sex-determining genes and mechanisms currently remain unknown.MethodsWe explored the sex-determination mechanism by integrating whole-genome sequencing, resequencing and comparative genomics approaches.ResultsIn this study, we employed HiFi and Hi-C sequencing technologies to construct a chromosome-level haplotypic genome assembly for male largemouth bass, with a genome size of 875.69 Mb. The assembled genome contains 23 chromosomes, covering 95.31% of the complete sequences with a high scaffold N50 of 35.93 Mb. A genome-wide association study (GWAS) of sex was performed with four populations consisting of 62 males and 58 females. For the sex trait, a total of 3,838 SNP loci were identified to be significantly associated with sexual discrepancy. Interestingly, almost all these significant SNPs (3,825) were clustered on chromosome 10 (Chr10), within a 3.5-Mb sex-determination region (SDR). They were homozygous in females while heterozygous in males. We therefore speculate that largemouth bass owns a XX/XY sex determination system. By comparing genomics data and examining coverage depth of resequencing reads, we revealed a 51-kb male-specific region (MSR) on Chr10. Gene annotation discovered a coding sequence (msy) within MSR-1, which may contribute to sex determination of largemouth bass. By differential expression analysis, two candidate sex-determining genes (ccdc103 and jockey) were predicted within the target SDR. Moreover, we applied two male-specific non-coding fragments (within MSR-2 and MSR-3) to design specific sex markers, successfully obtaining universal gender identity in examined largemouth bass.DiscussionOverall, our findings improve our understanding of the molecular basis for sex determination in largemouth bass, which will thereby promote the mono-sexual breeding progress in the aquaculture industry.